First-line nivolumab plus ipilimumab in pleural mesothelioma: efficacy and safety data from the real-world MesoNet study - Shah, Rajiv; Buchmeier, Eva L.; Kopp, Hans-Georg; Christoph, Daniel C.; Griesinger, Frank; Reck, Martin; Hoffknecht, Petra; Kuon, Jonas; Frost, Nikolaj; Grohé, Christian; Faehling, Martin; Luan, Jingting; et al. (Lung cancer, 2025)
Background - Despite the approval of nivolumab/ipilimumab, the prognosis of patients with pleural mesothelioma (PM) remains poor. Although this combination has shown improved survival in the landmark CheckMate (CM)-743 trial, evidence from real-world settings remains limited. - Methods - In this retrospective, multicenter study, the outcome and safety data for 135 consecutive patients with first-line nivolumab/ipilimumab were evaluated among 1,575 adult patients with PM from 12 German cancer centers. Radiologic response and progression were analyzed according to the revised modified RECIST criteria. - Results - The median overall survival (OS) was 13.1 months for the unselected real-world cohort, and 15.5 months for CM-743-eligible patients (16.7 months for the non-epithelioid and 10 months for the epithelioid subtypes). Patients who experienced partial responses to nivolumab/ipilimumab had significantly longer survival than those without (24 months vs. 10.3 months; p = 0.00026). 37 % of patients experienced immune-related adverse events (irAEs), among whom 58 % had grade 3/4 toxicity. IrAEs of any grade were associated with longer survival (17.3 months vs. 11.7 months for patients without irAEs; p = 0.022). Furthermore, grade 1/2 irAEs were associated with even better outcomes when compared to grade 3/4 toxicities (22.7 months vs. 16.7 months median OS) and absence of toxicity (p < 0.0167 for trend). - Conclusions - Overall survival with first-line nivolumab/ipilimumab in the real-world setting is comparable to the CM-743 results among trial-eligible patients, especially with non-epithelioid tumors, but shorter for the unselected cohort. IrAEs, in particular those of low-grade, were associated with better outcomes. In the absence of predictive biomarkers and with few therapeutic options available, both dual checkpoint blockade and platinum-pemetrexed chemotherapy remain viable first-line regimens.
Online verfügbar: 5. August 2025, Artikelversion: 7. August 2025
Gesehen am 21.01.2026